Pengaruh leverage, profitabilitas, ukuran perusahaan, dan kebijkan dividen terhadap nilai perusahaan - Putri, Melati Efesia; Sunarto, Sunarto (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This research was done to know the effect of variables of leverage, profitability, company size, and dividend policy on company value. The object of the research are companies on the Indonesia Stock Exchange listed on the LQ45 index 2016-2020 period. The data used is quantitative secondary data, taken from the financial statement data for the 2016-2020 period. The method used in this research is multiple linear regression model. The final sample that was get totally 168 observations from 68 LQ45 index companies. Tobin's Q measurement is used in measuring company value. Ratio calculation of variable leverage Debt to Equity Ratio, calculation of profitability variables using ROA Return on Total Assets, calculation of dividend policy using Dividend Payout Ratio, and the calculation of firm value using the formula ln(total assets). The results from this research are profitability positive influence on company value and company size is significantly positive on company value, while leverage does not affect on company value and no significant policy of company.